EFFECTS OF DOLLARIZATION ON ECUADOR'S TRADE FLOWS: A GRAVITY MODEL APPROACH - Garc?a Hinojosa, Pa?l Alejandro (2014)
Since Ecuador adopted the US dollar as its domestic currency in 2000, several economic sectors have discussed its real effects on Ecuador?s economy mainly on its external sector. This study estimates the impact that dollarization has had on Ecuador?s bilateral trade flow with 20 of its main trade partners from 1986 to 2013. By using the Gravity model of trade (well-known tool of predicting bilateral trade among countries) I have found positive and significant estimates for the Dollar dummy variables included in the respective models. The results suggest that Ecuador?s trade flows have nearly doubled in average since the dollarization was introduced furthermore its effect is more significant on Ecuador?s imports than on its exports.